PENGARUH PELAYANAN, PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA KONTER AHMADI CELL DI KECAMATAN BESUKI KABUPATEN SITUBONDO - Susilowati, Diana; Karnadi, Karnadi; Soeliha, Siti; A, Muhammad Iqbal (Growth, 2022)
The results of multiple linear regression indicate that the service variable (X1), product (X2), and promotion (X3) have a positive influence on the purchasing decision variable (Y). it is shown in the results of multiple linear regression analysis Y= -2.775E-16 + 0.562X1 + 0.258X2 + 0.183X3 + e which shows the value for the service variable is tcount 7.274 > ttable 1.985. it means that the service variable has a partial effect on purchasing decisions. The value for the product variable is tcount 4.463 > ttable 1.985. This means that the product variable has a partial effect on purchasing decisions. The value for the promotion variable is tcount 2,531 > ttable 1,985. This means that the promotion variable has a partial effect on purchasing decisions at the Ahmadi Cell Counter located in Besuki District, Situbondo Regency. The F test shows the Fcount 136.964 > Ftable 2.70, so it can be concluded that the Service, Product and Promotion variables have a simultaneous effect on purchasing decisions. Based on the dominant test, the value of the Service variable is greater than the other variables of 7.274. The coefficient of determination or R square shows a value of 0.812. from these results it can be concluded that all independent variables (Services, Products and Promotions) have a contribution of 81.2% to the dependent variable (purchase decisions) with a level of influence "Very strong", and the remaining 18.8% is influenced by these variables. ot.